2016
DOI: 10.4103/0973-6247.187940
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the economic burden in management of Guillain–Barre syndrome using modified plasmapheresis

Abstract: Background:Guillain–Barre syndrome (GBS) is an autoimmune acute inflammatory demyelinating polyneuropathy affecting the peripheral nervous system treated with high-dose immunoglobulin, physical therapy, or plasmapheresis. Immunoglobulins are expensive and even plasmapheresis might not be affordable to patients visiting government set-ups.Aims:This study was undertaken to emphasize the efficacy of plasmapheresis in treatment of adult GBS patients and to narrate methods of reducing the economic burden in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This situation underscores the need for low-cost and effective treatment strategies for GBS in LMIC. Small volume plasma exchange (SVPE) is a novel, relatively low cost (~$500), simple technique for selective removal of plasma, and has been shown to be a safe and feasible treatment for GBS in resource-limited settings such as India and Bangladesh 18 , 110 . However, as the efficacy of SVPE has only been shown in a small number of patients, large-scale studies are required before this technique can be implemented in routine clinical practice.…”
Section: Treatmentmentioning
confidence: 99%
“…This situation underscores the need for low-cost and effective treatment strategies for GBS in LMIC. Small volume plasma exchange (SVPE) is a novel, relatively low cost (~$500), simple technique for selective removal of plasma, and has been shown to be a safe and feasible treatment for GBS in resource-limited settings such as India and Bangladesh 18 , 110 . However, as the efficacy of SVPE has only been shown in a small number of patients, large-scale studies are required before this technique can be implemented in routine clinical practice.…”
Section: Treatmentmentioning
confidence: 99%
“…Recently published comparative and noncomparative studies of GBS outcomes after treatment with TPE and/or IVIG have consisted primarily of case reports or case series from single institutions in developing countries, at which the choice between TPE and IVIG is largely dependent on economic considerations . Given the established equivalence between TPE and IVIG as effective treatments for GBS, it is important to evaluate patient‐ and hospital‐level characteristics that may affect treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…In serious GBS, 6 meetings are no superior to 4. In accordance with these discoveries, Yuki et al revealed that in any event 2 PE are expected to fundamentally decrease the coursing immunoglobulin complexes 27 . Besides IVIg and plasma trade, no different strategies or medications have been demonstrated successful in the treatment of GBS.…”
Section: Plasmapheresismentioning
confidence: 78%